DNA Data Bank of Japan (DDBJ) update report 2022. Issue Volume 51:Issue D1(2023) (24th November 2022) - Tanizawa, Yasuhiro; Fujisawa, Takatomo; Kodama, Yuichi; Kosuge, Takehide; Mashima, Jun; Tanjo, Tomoya; Nakamura, Yasukazu
Abstract: The Bioinformation and DNA Data Bank of Japan (DDBJ) Center (https://www.ddbj.nig.ac.jp ) maintains database archives that cover a wide range of fields in life sciences. As a founding member of the International Nucleotide Sequence Database Collaboration (INSDC), our primary mission is to collect and distribute nucleotide sequence data, as well as their study and sample information, in collaboration with the National Center for Biotechnology Information in the United States and the European Bioinformatics Institute. In addition to INSDC resources, the Center operates databases for functional genomics (GEA: Genomic Expression Archive), metabolomics (MetaboBank), and human genetic and phenotypic data (JGA: Japanese Genotype–Phenotype Archive). These databases are built on the supercomputer of the National Institute of Genetics, whose remaining computational capacity is actively utilized by domestic researchers for large-scale biological data analyses. Here, we report our recent updates and the activities of our services.